2019
DOI: 10.1128/mbio.00128-19
|View full text |Cite
|
Sign up to set email alerts
|

Core Fucosylation of Maternal Milk N-Glycan Evokes B Cell Activation by Selectively Promoting thel-Fucose Metabolism of GutBifidobacteriumspp. andLactobacillusspp

Abstract: The maternal milk glycobiome is crucial for shaping the gut microbiota of infants. Although high core fucosylation catalyzed by fucosyltransferase 8 (Fut8) is a general feature of human milk glycoproteins, its role in the formation of a healthy microbiota has not been evaluated. In this study, we found that the core-fucosylated N-glycans in milk of Chinese mothers selectively promoted the colonization of specific gut microbial groups, such as Bifidobacterium spp. and Lactobacillus spp. in their breast-fed infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 80 publications
0
64
1
Order By: Relevance
“…in neonatal mice fed by the control and GDM mice was also compared, a decreasing pattern was found in GDM‐C offspring (Figure S4). As Bifidobacteria and Lactobacillus are the major microbial genera in gut of the healthy breast‐fed infants, they play important beneficial roles in regulating the growth and the immune development of the newborns, the decreasing of these bacteria may suggest an unfavorable status for infant health. On the contrary, the abundance of Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in neonatal mice fed by the control and GDM mice was also compared, a decreasing pattern was found in GDM‐C offspring (Figure S4). As Bifidobacteria and Lactobacillus are the major microbial genera in gut of the healthy breast‐fed infants, they play important beneficial roles in regulating the growth and the immune development of the newborns, the decreasing of these bacteria may suggest an unfavorable status for infant health. On the contrary, the abundance of Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%
“…34 Studies from our group and others have shown relationships between milk N-glycans and the gut microbiome of breast-fed infants, which can affect their immune responses. [35][36][37] GDM is associated with a high risk of adverse consequences, including the inhibition of immune tolerance formation in infants. [38][39][40] It has been suggested that GDM does not affect the abundance of HMOs but alters the glycosylation patterns of N-glycans in human milk.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Lactobacillus gasseri ATCC 33323, which carries a gene cluster with asnA2, pepV, and alfR2 (Fig. 7), was recently shown to grow with 6=FN and N2F N-glycan (25). However, in the same work, L. casei ATCC 334 was reported to use L-fucose, which is contradictory to the fact that no fuc genes are present in its genome (60).…”
Section: Discussionmentioning
confidence: 95%
“…In commensal bacteria, the ability to remove N-glycans from glycoproteins has been described in a few Bifidobacterium species (23,24). Recently, the importance of core-fucosylated N-glycans from human milk in promoting the intestinal growth of Bifidobacterium and Lactobacillus species has been demonstrated in lactating infants from mothers carrying different alleles of the fucosyltransferase Fut8, responsible for core fucosylation (25). This provides the first in vivo evidence of the importance of this core structure in feeding intestinal commensals.…”
mentioning
confidence: 77%
See 1 more Smart Citation